Trash management policy based on participation of the society - Indah Kusuma Dewi (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
The trash problem that is currently happening certainly requires special handling by both the government and the community. If the trash management is not in accordance with the methods and techniques of trash management that are environmentally sound, it is feared that it will get negative impacts such as a decrease in the quality of the environment which will also have an impact on public health. The purpose of this study was to determine how to identify trash management problems in Napa Village, Mawasangka District, Central Buton Regency and to find out how the concept of trash management in Napa Village, Mawasngka District, Central Buton Regency. This type of research is empirical juridical research. The results showed the identification of trash management problems in Napa Village including identification of trash problems in Napa Village, concept of 3 (three) R trash and trash processing methods in Napa Village. The concept of regulating trash management in Napa Village, namely analysis of laws and regulations on trash, philosophical studies of trash in Napa Village, juridical studies of trash in Napa Village, sociological studies of trash in Napa Village, study of direction and scope of trash management arrangements in Napa Village , Academic Manuscripts of Village Regulations on Trash Management in Napa Village and Draft Village Regulations on Trash Management in Napa Village.